Identification of circulatory microRNA based biomarkers for early pregnancy diagnosis in buffalo - Batra, Kanisht; Sehrawat, Anju; Kumar, Aman; Singh, Man; Kaur, Ramandeep; Yadav, Dipin Chander; Singh, Neha; Maan, Sushila (Frontiers in Cell and Developmental Biology, 2024)
The most crucial factor in improving animal reproduction efficiency is early pregnancy diagnosis. Early diagnosis not only reduces the time interval between two calvings but also aids farmers in identifying open animals, thereby preventing significant milk production losses.Therefore, the objective of this study was to discover circulatory miRNAs that would be useful for early pregnancy diagnosis in buffalo. Blood samples were taken on 0, 6 th , 12 th , and 18 th day after artificial insemination from pregnant animals (n = 30) and non-pregnant animals (n = 20).During these stages of pregnancy, total RNA was extracted, and a small RNA library was subsequently generated and sequenced on the Illumina platform. Subsequently, Real-time PCR was used to validate the findings. There were 4022 miRNAs found during the pregnancy, with 15 of those lacking sequences and 4007 having sequences already in the database. From the beginning of pregnancy until the 18 th day, 25 of these miRNAs showed a substantial shift in expression levels in the maternal blood, with a change more than 2 logs. Furthermore, based on qPCR results, 19 miRNAs were found to be more abundant in pregnant animals than in nonpregnant animals. We used target prediction analysis to learn how maternally expressed miRNAs relate to fetal-maternal communication. In conclusion, miRNA based biomarkers that could be associated with the diagnosis of pregnancy were identified including miR-181a and miR-486 highly up regulated on the 18 th day of pregnancy. This study also provides a comprehensive profile of the entire miRNA population in maternal buffalo blood during the early stages of pregnancy.